Climate resilient agriculture to combat food and nutritional security - Singh, Vinod Kumar; Prabhakar, M (Indian Farming, 2021)
Climate change impacts on crops, natural resources, livestock and fisheries was assessed and adaptation and mitigation technologies for various systems have been developed. The proven resilient technologies have been demonstrated in 151 climate resilient village clusters. The adaptation and mitigation practices are being upscaled by several State Governments across the country. Integrated approach at village level by implementing the package of climate resilient practices over years will immensely contribute to climate resilient agriculture and food and nutritional security in the country.